Rome victorious - Hoyos, Dexter. (London)
viii, 256 sayfa
Keywords: “Rome - Urbs Roma : city of patricians and plebeians, emperors and gladiators, slaves and concubines - was the epicentre of a far-flung imperium whose cultural legacy is incalculable. How a tiny settlement, founded by desperate adventurers beside the banks of the River Tiber, came to rule vast tracts of territory across the face of the known world is one of the more improbable stories of antiquity. The epic scale of the Colosseum; majestically columned temples; formidable legionaries marching in burnished steel breastplates; and capricious Caesars clad in purple robes who thought themselves gods: all these images speak of a grandeur that continues to be associated with this most celebrated of ancient capitals. However, as Dexter Hoyos reveals, the empire was not won cheaply or fast, and did not always succeed. The Carthaginian general Hannibal came close to destroying it. Arminius freed Germania by brutally annihilating three irreplaceable legions int he Teutoburg Forest - a disaster that broke Augustus' heart''-- Yayıncı.